Does attribution theory apply to football coaches' perception of competence? Factor analyses and comparisons between three European countries - Mitrotasios, M.; Varsamis, P. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
In order coaches to survive in the area of professional football they have to be successful [1]. The objective of this study is to show how successful do the coaches of three European countries consider their professional performance and what the causes are. In addi-tion, it checks the appropriateness of Weiner`s [5] basic model related to causes classification. Methods For this purpose a questionnaire has been made out [2, 3, 4]. It has been answered by 100 active coaches of the above two professional leagues Germany (n= 31), England (n=35) and Greece (n=35). Then results of this exploratory factor analysis pointed out four factors (loadings >.60) which explain the 62, 42% of the total variance and meet Möller`s model views, which is based on Weiner`s relevant theory, about causes classification in sports. Then the application of the confirmation factor analysis certified the good fit of the model consisted of four factors which are: a) personal abilities (internal invariable causes) b) further education (internal variable causes) c) management support, training-conditions, fa-cilities etc (external invariable causes) d) luck, opponents performance level (external vari-able causes). The paired-samples t-test was also applied for the means comparison between two variables. The covariance analysis, which included two others factors (country and league) and two covariates (age and training experience), was used for the rest comparisons. Pearson`s coefficient was also taken into account in order to estimate correlations between variables. Results The results indicated that the majority of coaches (81%) consider their professional career definitely successful. Any significant differences among the three questioned countries and the two professional leagues were not noticed (p>.10). In addition, it was found out that coaches attribute their success more to internal factors and less to the correspondent external ones (M=3.69 and M=2.95, t(99)=14.21 p<001). Moreover it was established that only the internal invariable causes are strongly related to evaluation of their career as successful (r=.369, p<.001). Discussion In conclusion the results of this study show that professional football coaches, irrespective of country and league, consider that the qualities of their personality as the ability to lead a team, the experience and the knowledge demanded for a team`s training, the educa-tion acquired in sport schools and their constant further education in seminars (internal invari-able and variable causes) help them to carry out their training program in professional championship satisfactorily, in contrast to the external factors (luck, opponents performance level, training condition and facilities). This fact proves the significance of success in the profes-sional football area. Finally further research is needed for checking the appropriateness of other models related to causal attribution and perception of professional success.